Perlindungan Hukum Pekerja Perjanjian Kerja Waktu Tertentu Pada PT. Wonokoyo Jaya Corp - Mohammad Hatta; Purwono Sungkowo Raharjo; Rosita Candrakirana (Fakultas Syariah Institut Agama Islam Negeri Palu, 2023)
Problems regarding the rights of workers/labourers who work in a company are still not fully fulfilled, especially for workers with a certain time work agreement system (PKWT). Therefore, the government issued implementing regulations for the Omnibus Law on the Job Creation Law, namely PP No. 35 of 2021 concerning PKWT, outsourcing, working time, work relations and rest time, and termination of employment (PHK) as an effort to realize the welfare of workers. However, in practice, there are still many companies that have not fully fulfilled their workers' rights. Based on this background, a study was compiled entitled